Penentuan Pengendalian Persediaan Menggunakan Metode P Lost Sales Probabilistik (Studi Kasus : Toko Rizky Bandar Lampung) - Rafi, Muhammad; Suharto, Suharto; Nudin, Burhan; Sundari, Susanti (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
As a distributor, Rizky Pasar Tengah stores tend to pay less attention to inventory problems, so that consumer demands often cannot be met optimally. Therefore, Toko Rizky Pasar Tengah requires more optimal inventory control calculations. This research aims to test appropriate inventory control for stores, so that total inventory costs can be minimized. This research uses a simple probabilistic method and the P Lost sales model. based on the results of data processing, the total cost difference between inventory control carried out by the shop using the simple the P Lost sales Probabilistic method, for the cv. simple, and cost reduction of 11% using the P Lost sales Probabilistic model with a difference of IDR 72,041,858.-. of the total costs incurred by the shop amounting to Rp. 660,241,415,- in a period of 3 months. Keywords: P lost sales, Probabilistic, Rizky Bandar Lampung stores